2004
DOI: 10.1177/039463200401700114
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Combination of N-Acetylcysteine and Ribavirin to Protect from Lethal Influenza Viral Infection in a Mouse Model

Abstract: Oxidative stress is implicated in the pathogenesis of pulmonary damage during viral infections. In a previous study we observed a significant improvement of survival of influenza-infected mice with NAC, 1g/kg divided in two daily administrations, for 8 days including a pretreatment on day 1 before infection. In order to test NAC in a more realistic model, we studied the effect of combined treatment with NAC and the antiviral drug, ribavirin. Since in the present work we wanted to test a possible synergistic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 20 publications
2
49
0
1
Order By: Relevance
“…Administration of NAC significantly decreased the mortality in mice infected with influenza virus [49], and a combination of NAC and ribavirin synergistically reduced the lethal effects [50]. Furthermore, a combination of NAC and oseltamivir also synergistically reduced the lethal effect of influenza virus infection in mice [51].…”
Section: Superoxide Dismutasesmentioning
confidence: 99%
“…Administration of NAC significantly decreased the mortality in mice infected with influenza virus [49], and a combination of NAC and ribavirin synergistically reduced the lethal effects [50]. Furthermore, a combination of NAC and oseltamivir also synergistically reduced the lethal effect of influenza virus infection in mice [51].…”
Section: Superoxide Dismutasesmentioning
confidence: 99%
“…Surprisingly, little is known regarding the oxidative stress response in patients with virally induced lung inflammation. In an animal model of influenza infection, inhibition of oxygen radicals through administration of antioxidants or increased lung superoxide dismutase levels significantly reduced lung injury and improved the survival rate of infected animals, suggesting that oxidative stress can play a significant role in the pathogenesis of virally induced pneumonia (13)(14)(15)(16)(17). We have previously shown that RSV induces reactive nitrogen species and nitric oxide synthase (NOS) in the lungs of infected mice, and that inhibition of NOS expression significantly reduces RSV-induced lung inflammation (18).…”
mentioning
confidence: 99%
“…Vitamine E combined with rimantadine significantly reduced oxidative stress and lung lesions during influenza infection in mice (54). The antioxidant molecule N-acetylcysteine (NAC) in combination with ribavirin and oseltamivir showed enhanced survival of mice against a lethal influenza virus infection (25,27). Rimantadine with polyphenol complex extracted from G.sanguineum (26) and eventually a triple combination with some biological response modifiers: amantadine, ribavirin and human interferon-α, have been proved the advantages of such an approach (36).…”
Section: Combination Therapy With Biological Response Modifiers (Bmrsmentioning
confidence: 99%
“…Both bind the M2 proton channel and prevent the influx of H+ ions into the virion, a process crucial for the uncoating stage of the virus replication cycle (37). The sites of interaction between the viral target and the inhibitors are well studied -they are positions 26,27,30,31,34 in the transmembrane region. These are amino acid residues which contact with the drug molecule.…”
Section: Introductionmentioning
confidence: 99%